Martin Gardner in the twenty-first century - Henle, Michael; Hopkins, Brian (Mathematical Association of America, 2012)
"This book collects articles Gardner wrote for the MAA in the twenty-first century, together with other articles the MAA published from 1999-2012 that spring from and comment on his work"--Cover